2016
DOI: 10.1186/s12977-016-0249-x
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted functions and roles of HBZ in HTLV-1 pathogenesis

Abstract: Human T cell leukemia virus type 1 (HTLV-1) is an oncogenic retrovirus responsible for the development of adult T-cell leukemia (ATL). Although HTLV-1 harbors an oncogene, tax, that transforms T cells in vitro and induces leukemia in transgenic mice, tax expression is frequently disrupted in ATL, making the oncogenesis of ATL a bit mysterious. The HTLV-1 bZIP factor (HBZ) gene was discovered in 2002 and has been found to promote T-cell proliferation and cause lymphoma in transgenic mice. Thus HBZ has become a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
129
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(134 citation statements)
references
References 96 publications
3
129
0
2
Order By: Relevance
“…The HTLV-1 antisense genomic strand encodes a basic leucine zipper (bZIP)-containing protein, designated HBZ. Although HTLV-1 is capable of infecting different cell types in vitro , HBZ protein is mainly detected in CD4 + T cells in vivo [3, 24, 25]. This cell-type specific expression of HBZ has been shown to play a variety of roles in the pathogenesis of HTLV-mediated T-cell leukemia (reviewed in [3, 26]).…”
Section: Antisense Transcription Among Exogenous Retrovirusesmentioning
confidence: 99%
See 2 more Smart Citations
“…The HTLV-1 antisense genomic strand encodes a basic leucine zipper (bZIP)-containing protein, designated HBZ. Although HTLV-1 is capable of infecting different cell types in vitro , HBZ protein is mainly detected in CD4 + T cells in vivo [3, 24, 25]. This cell-type specific expression of HBZ has been shown to play a variety of roles in the pathogenesis of HTLV-mediated T-cell leukemia (reviewed in [3, 26]).…”
Section: Antisense Transcription Among Exogenous Retrovirusesmentioning
confidence: 99%
“…Although HTLV-1 is capable of infecting different cell types in vitro , HBZ protein is mainly detected in CD4 + T cells in vivo [3, 24, 25]. This cell-type specific expression of HBZ has been shown to play a variety of roles in the pathogenesis of HTLV-mediated T-cell leukemia (reviewed in [3, 26]). For instance, HBZ transforms T-cells into a cancerous phenotype, in part by enhancing the expression of chemokine receptor CCR4 in this cell type, which promotes T-cell proliferation and migration [27].…”
Section: Antisense Transcription Among Exogenous Retrovirusesmentioning
confidence: 99%
See 1 more Smart Citation
“…HBZ is considered to play an important role in the oncogenic process because of its ability to drive infected cell proliferation, to increase hTERT transcription, to inhibit apoptosis, and to disrupt host genomic integrity depending on several HBZ-induced microRNAs (miRNAs). 17,[26][27][28] …”
Section: Introductionmentioning
confidence: 99%
“…Also, HBZ contains a functional nuclear export signal motif within its N-terminal region and can shuttle between the cytoplasm and nucleus (22). Previous reports showed that HBZ interacts with various cellular factors and modulates their functional activities in both the cytoplasmic and nuclear compartments (22,23). In contrast to Tax, HBZ is constitutively expressed in all ATL patient samples because its 3= LTR is conserved and unmethylated in ATL patient cells (24,25).…”
mentioning
confidence: 99%